Development of equations to estimate microbial contamination in ruminal incubation residues of forage produced under tropical conditions using 15N as a label1 - Machado, P. A S; Valadares Filho, S. C.; Detmann, E.; Santos, S. A.; Valadares, R. F D; Ducatti, C. [UNESP]; Rotta, P. P.; Costa e Silva, L. F. (Oxford University Press (OUP), 2013)
The objective of this study was to use 15N to label microbial cells to allow development of equations for estimating the microbial contamination in ruminal in situ incubation residues of forage produced under tropical conditions. A total of 24 tropical forages were ruminal incubated in 3 steers at 3 separate times. To determine microbial contamination of the incubated residues, ruminal bacteria were labeled with 15N by continuous intraruminal infusion 60 h before the first incubation and continued until the last day of incubation. Ruminal digesta was collected for the isolation of bacteria before the first infusion of 15N on adaptation period and after the infusion of 15N on collection period. To determine the microbial contamination of CP fractions, restricted models were compared with the full model using the model identity test. A value of the corrected fraction A was estimated from the corresponding noncorrected fraction by this equation: Corrected A fraction (ACPC) = 1.99286 + 0.98256 × A fraction without correction (ACPWC). The corrected fraction B was estimated from the corresponding noncorrected fraction and from CP, NDF, neutral detergent insoluble protein (NDIP), and indigestible NDF (iNDF) using the equation corrected B fraction (BCPC) = -17.2181 - 0.0344 × fraction B without correction (BCPWC) + 0.65433 × CP + 1.03787 × NDF + 2.66010 × NDIP - 0.85979 × iNDF. The corrected degradation rate of B fraction (kd)was estimated using the equation corrected degradation rate of B fraction (kdCPC) = 0.04667 + 0.35139 × degradation rate of B fraction without correction (kdCPWC) + 0.0020 × CP - 0.00055839 × NDF - 0.00336 × NDIP + 0.00075089 × iNDF. This equation was obtained to estimate the contamination using CP of the feeds: %C = 79.21 × (1 - e-0.0555t) × e-0.0874CP. It was concluded that A and B fractions and kd of CP could be highly biased by microbial CP contamination, and therefore these corrected values could be obtained mathematically, replacing the use of microbial markers. The percentage of contamination and the corrected apparent degradability of CP could be obtained from values of CP and time of incubation for each feed, which could reduce cost and labor involved when using 15N. © 2013 American Society of Animal Science. All rights reserved.
Keywords: Cattle; Degradability; Protein fractions; Rumen degradable protein